Simulation of Tax Planning in Operating Cash Flow (Revista Brasileira de Contabilidade e Gestão, 2023)
Objective: To simulate the projection of tax planning operating cash flow (OCF) at a telecommunications company (call center) by inserting four legal possibilities to find which generates less disbursement in the flow of operations and how the balance responds to these situations. Method: Based on Vicente (2005), a functionalist simulation incubator model was instrumentalized by the semi structure of empirical evidence and a real context, which enabled this study to build its objective scenario and conditions. Results: In view of tax regimes and benefits, applying tax planning to the FCO saved BRL 120.328,55, with a 7.21% positive variation between projections a) and d). Contributions: This study instrumentalized a viable tool to reduce the difficulties related to working capital and high tax burden, variables that compromise the survival of small- and medium-sized enterprises (SMEs). It found that simulating cash flow statements (CFS) subsidizes decision-making in SMEs and that tax benefits, such as payroll exemption and minimum ISSQN (the Brazilian tax over services of any nature) rates save financial resources. Finally, it confirms the ability of tax planning to reduce corporate spending. Therefore, managers, researchers, and interested students are expected to replicate, refute, and criticize the model to add value and enable SMEs to have access to more tangible tools and easy understanding of financial planning and control.
Keywords: financial planning; tax planning; DFC; simulation